Growth and Yield of Chickpea as Affected by Detopping Time and Height (Bangladesh Agronomy Journal, 2022)
The production area of chickpea in Bangladesh is decreasing day by day due to the competition with higher yielding crop which is/or profitable than chickpea. As such, the experiment was undertaken at Regional Agricultural Research Station, Jashore during 2019-2020 and 2020-2021 to study the effect of most suitable method of de-topping (nipping) in chickpea (var. BARI Chola-10) for its growth and yield improvement. Treatments were imposed in a split-plot design where in main plot : time of nipping : 30 days after emergence (DAE) , 40 DAE E3- 50 DAE and in sub-plot: different heights of nipping practices: Control, Nipping 5 cm from growing tip, Nipping 8 cm from growing tip and Nipping 10 cm from growing tip. In interaction treatment, the highest days to flower (68), days to mature (112), vegetable yield (703 kg ha-1) was observed when chickpea plants were de-topped after 50 DAE at 10 cm from growing tip. The highest plant height (46 cm) was observed when de-topping at 40 DAE was done at 10 cm from growing tip. Seed yield (1419.95 kg ha-1) and Marginal Benefit Cost Ratio (MBCR) (13.1) was recorded maximum when chickpea plants de-topped 50 DAE at 5 cm from growing tip. De-topping practices in chickpea (var. BARI Chola-10) after 50 DAE at 5 cm from growing tip could maximize the productivity of chickpea.Bangladesh Agron. J. 2021, 24(2): 109-113